The idea of moral autonomy in the ethics of Hermann Cohen. [Spanish] (2010)
In this paper the aim is to reconstruct the rationale of moral autonomy in Hermann Cohen´s ethics. In order to achieve this aim, I consider the complexity of the concept of moral autonomy at its four levels. Mi hypothesis is that Cohen´s argumentation goes from the formal abstraction of the self-legislation to the concrete moment of the selfpreservation. I analyze then Eggert Winter´s critic of Cohen´s concept of moral autonomy, who questions the integration of the levels of the particularity and the universality in this fundamental moment of the theory. Against Winter I argue that Cohen´s process of argumentation succeeds in connecting the different levels of the concept of moral autonomy.